National Capacity Self Assessment for Non-Annex I Nations: The Case of Lebanon - Chaaban, Farid B.; Akkawi, Mohammad (International Journal of Energy Economics and Policy, 2013)
Countries, both developed and developing, are called on to identify, through self assessments, their priority environmental issues such as mitigating greenhouse gas emissions, combating deforestation, promoting sustainable land and water management, and minimizing their vulnerabilities to the impact of climate change. Root cause analysis is conducted to determine the major barriers and institutional capacities. This papers presents capacity constraints in national priority issues typically encountered in developing or non-annex one nations, with the national capacity self assessment of Lebanon taken as a case study. The analysis of the information has identified a number of achievements and difficulties related to the fulfillment of the commitments under the UN Framework Convention on Climate Change. The common priority issues are national action plan for GHG abatement, vulnerability and adaptation, research and systematic observation, technology transfer, and education and public awareness. Root cause analysis related to priority issues has been carried out during which the causes and impacts of the constraints have been identified. The corresponding assessment matrices are also presented. Lack of financial resources is found to be the constraint facing priority issues. Keywords: Power sector; self assessment; capacity development; root cause analysis; market penetration. JEL Classifications: O13; O53